conceptual model of root hair ideotypes for future agricultural environments: what combination of traits should be targeted to cope with limited P availability? - Brown, L. K; George, T. S; Dupuy, L. X; White, P. J (Annals of botany, 2013)
BackgroundPhosphorus (P) often limits crop production and is frequently applied as fertilizer; however, supplies of quality rock phosphate for fertilizer production are diminishing. Plants have evolved many mechanisms to increase their P acquisition, and an understanding of these traits could result in improved long-term sustainability of agriculture. This Viewpoint focuses on the potential benefits of root hairs to sustainable production.ScopeFirst the various root-related traits that could be deployed to improve agricultural sustainability are catalogued, and their potential costs and benefits to the plant are discussed. A novel mathematical model describing the effects of length, density and longevity of root hairs on P acquisition is developed, and the relative benefits of these three root-hair traits to plant P nutrition are calculated. Insights from this model are combined with experimental data to assess the relative benefits of a range of root hair ideotypes for sustainability of agriculture.ConclusionsA cost–benefit analysis of root traits suggests that root hairs have the greatest potential for P acquisition relative to their cost of production. The novel modelling of root hair development indicates that the greatest gains in P-uptake efficiency are likely to be made through increased length and longevity of root hairs rather than by increasing their density. Synthesizing this information with that from published experiments we formulate six potential ideotypes to improve crop P acquisition. These combine appropriate root hair phenotypes with architectural, anatomical and biochemical traits, such that more root-hair zones are produced in surface soils, where P resources are found, on roots which are metabolically cheap to construct and maintain, and that release more P-mobilizing exudates. These ideotypes could be used to inform breeding programmes to enhance agricultural sustainability.